"Den kunne da ikke sådan bare blive væk" – En korpusstudie i oversættelsen af danske diskurspartikler til svensk - Arvidsson,Jonas (2024)
In this bachelor thesis, I examine how professional translators handle the Danish discourse particles da, nok, and sgu in translations of Danish fiction texts into Swedish. Of particular interest is how the omission of these discourse particles affects the stylistic character of the text and what implications this has for the reader's experience of the target text. My corpus consists of four Danish works in various genres and their translations into Swedish. The theoretical framework primarily relies on Eugene Nida's theory of equivalence. The translations were categorized into three groups – formally equivalent, dynamically equivalent, and missing translation – and the results indicate that only about half of the particles were translated, primarily into formally equivalent translations. When the discourse particles are not translated, it can result in a loss of emotional nuance, altered tone, and a loss of communicative function, undermining reader engagement.
Keywords: discourse particles; da; nok; sgu; translation; equivalence; lost in translation